2013
DOI: 10.3109/0142159x.2013.804909
|View full text |Cite
|
Sign up to set email alerts
|

The use of social-networking sites in medical education

Abstract: Social-networking sites have been employed without problems of professionalism, and received positive feedback from learners. However, there is no solid evidence base within the literature that social-networking is equally or more effective than other media available for educational purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(88 citation statements)
references
References 14 publications
1
80
0
7
Order By: Relevance
“…However, Roy et al also found that although concerns over professionalism existed, there was not actually any concrete evidence of unprofessional behaviour when social media was implemented correctly. Cartledge et al (2013) came to the same conclusion and even contacted the authors of the papers included in their study, of whom none could report any actual event of unprofessionalism. There may be however a certain amount of publication bias with editors only publishing articles with positive outcomes (Cartledge et al, 2013).…”
Section: Positive Impact Of Social Mediamentioning
confidence: 99%
See 2 more Smart Citations
“…However, Roy et al also found that although concerns over professionalism existed, there was not actually any concrete evidence of unprofessional behaviour when social media was implemented correctly. Cartledge et al (2013) came to the same conclusion and even contacted the authors of the papers included in their study, of whom none could report any actual event of unprofessionalism. There may be however a certain amount of publication bias with editors only publishing articles with positive outcomes (Cartledge et al, 2013).…”
Section: Positive Impact Of Social Mediamentioning
confidence: 99%
“…Cartledge et al (2013) came to the same conclusion and even contacted the authors of the papers included in their study, of whom none could report any actual event of unprofessionalism. There may be however a certain amount of publication bias with editors only publishing articles with positive outcomes (Cartledge et al, 2013). Further quantitative studies are therefore needed to confirm or dispel the negative connotations linked to the use of social media within medical education.…”
Section: Positive Impact Of Social Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…Surgery personnel, like other professionals, use social media to share and communicate with family, friends, and their respected colleagues. This new technology provides easy access to rapid communication, faster networking, and instantaneous consultations and lectures [1]. As part of the Web 2.0, social media includes blogs, wikis, podcasts, and other networking options such as Facebook, Twitter, and LinkedIn.…”
Section: Introductionmentioning
confidence: 99%
“…Les réseaux sociaux ont été utilisés à des fins éducatives dans différentes disciplines concernant la santé, à différents niveaux d'enseignements et sur différents continents sans toutefois montrer ni une équivalence ni une supériorité par rapport aux autres médias utilisables [2] . Facebook est actuellement le représentant le plus utilisé et le plus complet des réseaux sociaux.…”
Section: Introductionunclassified